An introduction to transport and development - Hickman, R; Givoni, M; Bonilla, D; Banister, D (Edward Elgar, 2015)
This Handbook provides an extensive overview of the relationships between transport and development. With 45 chapters from leading international authors, the book is organised in three main parts: urban structure and travel; transport and spatial impacts; and wider dimensions in transport and development. The chapters each present commentary on key issues within these themes, presenting the debate on the impacts of urban structure on travel, the impacts of transport investment on development, and social and cultural change on travel. A multitude of angles are considered – leaving the reader with a comprehensive and critical understanding of the field